REMOTE WORK AND ITS IMPLICATIONS ON WORKER HEALTH - Sousa, Daiana Da Silva; Cammarosano, Marília (Revista Interface Tecnológica, 2023)
The present article aimed to discuss, through a review on the topic, the impacts of telecommuting on the physical and mental health of workers, taking into consideration historical events such as the COVID-19 pandemic and the technological revolution of Industry 4.0. The pandemic was a decisive factor that significantly propelled the adoption of remote work, emphasizing the importance of flexibility in the professional environment. The technological revolution of Industry 4.0 is transforming the nature of work and global connectivity. While flexible work offers significant opportunities, it also presents challenges, such as the expectation of continuous availability, job insecurity, and the need for constant adaptation to technological changes. As society adjusts to these changes, it is crucial to effectively balance these benefits and challenges to ensure that new work models have a positive impact. Finally, there is a strong argument for the importance of ensuring the right to disconnect as a fundamental element in protecting the basic rights of workers, with an emphasis on the right to health.